Strategi Peningkatan Daya Saing Agribisnis Madu Kelulut melalui Inovasi Pemasaran dan Hilirisasi Produk - I Putu Gede Didik Widiarta; Riki Andika; Qurratu Aini; Ananda Putra Agung; Cori Qamara (Yayasan Literasi Sains Indonesia, 2025)
Stingless bee honey agribusiness supports sustainable rural development and food security. Small-scale producers in Indonesia face challenges such as limited production capacity, weak branding, and low technological adoption. These barriers reduce their competitiveness in a rapidly expanding natural and functional food product market. This study aims to formulate strategies to enhance the competitiveness of stingless bee honey agribusiness through marketing innovation and product downstreaming in Lempake Village, Samarinda, East Kalimantan. Using a descriptive qualitative approach supported by SWOT (Strengths, Weaknesses, Opportunities, Threats) analysis, this research identifies key internal and external factors influencing business performance. The results show that the kelulut honey agribusiness is positioned in the progressive strategic quadrant (Quadrant I), with strong internal resources and favourable market opportunities. The main strengths lie in high product quality, sustainable local resources, and active farmer institutions, while weaknesses include limited technological capacity and low digital marketing literacy. Opportunities arise from the increasing demand for natural products and government support for downstreaming, whereas threats stem from market competition and fluctuating supply conditions. Strategic recommendations include strengthening digital branding, enhancing post-harvest and processing technology, fostering institutional collaboration, and promoting product diversification to increase added value. These strategies are expected to reinforce local competitiveness, promote sustainable agribusiness growth, and contribute to Indonesia’s long-term food security.